Visible-light-active unsymmetrical squaraine dyes with pyridyl anchoring groups for dye-sensitized solar cells - Deshmukh, Shivdeep Suresh; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Langmuir, 2023)
Visible-light-active alkyl group-wrapped unsymmetrical squaraine dyes SD1-SD3 were synthesized, featuring an indoline donor and pyridine and carboxylic acid anchoring groups. Their photophysical, electrochemical, and photovoltaic characteristics were examined by fabricating a dye-sensitized solar cell (DSSC) device. Both carboxylic acid and pyridine anchoring groups containing squaraine dyes SD3 and SD2 possess similar photophysical and electrochemical characteristics. However, their photovoltaic performances were completely different. The SD3 dye with the carboxylic acid anchoring group displayed a DSSC device efficiency of 7.20% (V-OC 0.81 V; J(SC) 12.29 mA/cm(2)) using iodolyte (I-/I-3(-)) electrolyte, compared to SD1 (V-OC 0.659 V; J(SC) 4.97 mA/cm(2); and eta - 2.34%) and SD2 (V-OC 0.629 V; J(SC) 1.68 mA/cm(2); and eta - 0.84%), which were featured with pyridyl anchoring groups. These results were attributed to dye loading on the Lewis and Br & oslash;nsted acidic sites of TiO2 and the importance of aggregated structures for photocurrent generation. In the incident photon-to-current efficiency (IPCE) analysis, SD1 dye-sensitized devices exhibited photocurrent generation from both monomeric and aggregated dyes on the TiO2 surface. In contrast, SD2 showed photocurrent generation solely from aggregated states. Despite the introduction of long alkyl chains to reduce dye aggregation and charge recombination, the results indicated preferential charge injection from only the aggregated SD2 dye on TiO2. Fluorescence-quenching experiments indicated an efficient charge transfer from the aggregated SD2 dye to TiO2 compared to that of the monomeric dye. Cosensitization, a method to enhance the light-harvesting efficiency and photocurrent generation in DSSCs, was explored by simultaneously cosensitizing pyridyl-based dyes (SD1 and SD2) with a blue-colored carboxylic acid-based squaraine dye SD4. IPCE analysis demonstrated that both SD1 and SD4 contributed to generating a photocurrent of 9.11 mA/cm(2). The sequential cosensitization of SD1 and SD4 with the coadsorbent CDCA showed the highest performance, with a V-OC of 0.663 V, a J(SC) of 11.43 mA/cm(2), and an efficiency (eta) of 5.20%.
Keywords: co-sensitization; Design; Emmision; Fluorescent Dyes; High-Efficiency; Organic Dye; Ring

Triazatruxene amine donor-based visible-light-responsive unsymmetrical squaraine dyes for dye-sensitized solar cells - Ingole, Kiran Balaso; Deshmukh, Shivdeep Suresh; Verma, Tushar Singh; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2024)
Optimized charge-transfer dynamics at the dye-TiO2/electrolyte interface are required for an enhanced dye-sensitized solar cell (DSSC) device performance. Such an optimized interface enhances the charge-injection, dye-regeneration, and diminished charge-recombination processes, synergistically enhancing the device efficiency. In this study, octupolar-structured sensitizers are designed to improve the interaction between the dye and the redox electrolyte for increasing the dye-regeneration process upon photoexcitation. Accordingly, a set of unsymmetrical squaraine dyes with indoline and triazatruxene amine donor-based D-A-D dyes are designed (KV1-KV3), synthesized, and sensitized with a semiconducting metal oxide (TiO2) film. The sensitizer forms a monolayer on the TiO2 surface, leading to a dye-dye interaction, which broadens the absorption spectrum. The N atom of the triazatruxene amine donor was left unsubstituted in KV1, whereas a hexyl chain was installed in KV2 and KV3 and a branched alkyl chain was installed on the core N atoms in KV3 to control the self-assembly of dyes on the TiO2 surface. Self-assembly of alkyl groups wrapped in KV1-KV3 dyes on the TiO2 surface aids surface passivation and broadens the absorption profile, improving the light-harvesting capabilities. The DSSC devices based on KV2 exhibited a high power conversion efficiency of 7.85% (V-oc = 794 mV, J(sc) = 14.76 mA/cm(2), and FF = 67%), with an onset incident photon-to-current conversion efficiency response from 680 nm.
Keywords: aggregationof dyes; Dye-sensitized solar cells; metal-free organic dyes; self-assembly of dye; squaraine dyes; triazatruxene

Far-red active squaraine dye-sensitized photoanode for dye-sensitized solar cells with a copper (II/I) electrolyte - Nawghare, Indrajeet S.; Deshmukh, Shivdeep Suresh; Joshi, Krati; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on TiO2 and charge recombination between electrons present in TiO2 and electrolyte can be achieved by wrapping the long alkyl groups around the dye structure and further introducing bulky donor on the dye is a potential approach to enhance both the open-circuit potential and short-circuit current parameters. Additionally, bulky donor containing dye structures modulates the photophysical and electrochemical properties of the sensitizer which helps reducing the over potentials required for the dye regeneration process by utilizing a multidentate ligand containing [Cu(tme)]2+/+ and I- /I3redox electrolytes. Hagfeldt donor appended far-red NIR active unsymmetrical squaraine dye (SQ-HF) has been designed, synthesized, and characterized. SQ-HF dye showed an intense absorption at 676 nm (epsilon 1.7 x 105 M- 1cm- 1). Photophysical and electrochemical studies indicated that the LUMO and HOMO energy levels of the SQ-HF dye were suited for charge injection (from the LUMO of the dye to the conduction band of TiO2) and dyeregeneration processes, respectively. The DSSC device efficiency of 5.15 % (JSC of 10.83 mA/cm2 and VOC of 0.690 V) has been achieved for SQ-HF dye by utilizing a literature reported [Cu(tme)]2+/+ and 4.11 % (JSC of 8.74 mA/cm2 and VOC of 0.702 V) in I- /I3- redox shuttles, respectively.
Keywords: aggregation of dyes; Bulky donor; dye-sensitized solar cell; Photocurrent generation; squaraine dye